Risk factors associated with Leishmania exposure among dogs in a rural area of Ilha Solteira, SP, Brazil - Pereira Spada, Julio Cesar [UNESP]; Silva, Diogo Tiago da [UNESP]; Alves, Maria Luana [UNESP]; Cardenas, Nicolas Cespedes; Inlamea, Osvaldo Frederico; Faria, Glaucia Amorim [UNESP]; Ferreira, Andrea Goncalves [UNESP]; Silva, Helio Ricardo [UNESP]; Ferreira de Sousa Oliveira, Tricia Maria; Starke Buzetti, Wilma Aparecida [UNESP] (Soc Brasileira Medicina Tropical, 2020)
Introduction: We sought to determine risk factors (RFs) associated with the presence of antibodies against Leishmania in dogs from a rural area of Ilha Solteira, SP, Brazil. Methods: Serum samples were collected from 250 dogs and tested using indirect enzyme-linked irrununosorbent assay (ELISA) and indirect immunofluorescence antibody tests (IFATs). Data concerning dogs, their environment, and their owners' knowledge of leishmaniasis were collected using a questionnaire. To determine RFs for contact with the parasite, univariate statistical analysis based on chi-squared and Fisher's exact tests, followed by logistic regression, was used. Results: It was found that 79/250 (31.6%) of the dogs were positive by IFAT, and 72/250 (28.8%) by ELISA. A total of 82/250 dogs (32.8%) were positive in at least one test. The RFs associated with occurrences of Leishmania exposure were large body size (OR = 2.25; 95% CI = 1.26-4.04; p = 0.003), presence of chickens (OR = 1.94; 95% CI = 1.05-3.65; p = 0.023), and lack of knowledge about Leishmania among dog owners (OR = 1.74; 95% CI = 0.96-3.21; p = 0.049). After multivariate analysis, the RFs for occurrence of Leishmania exposure in dogs that remained significantly associated were the dog's size (large dogs) (OR = 1.2; 95% CI = 1.06-1.35; p = 0.003) and presence of chickens on the properties (small farms) (OR = 1.15; 95% CI = 1.02-1.30: p = 0.023). Conclusions: These results may be useful for improving preventive practices to reduce the incidence of Leishmania exposure among dogs in rural areas.
Keywords: Risk factors; Leishmania; Dogs; Rural area